PENGARUH STRATIFIKASI SOSIAL TERHADAP PELAYANAN PUBLIK DI KANTOR DESA KALOSI KECAMATAN DUA PITUE KABUPATEN SIDENRENG RAPPANG - Rastillah Rastillah (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Abstract The purpose of this study is to determine the effect of social stratification at the Kalosi Village Office in Duapitue Sub-district, Sidenreng Rappang Regency and to determine the factors that influence social stratification on public services at the Kalosi Village Office in Duapitue Sub-District, Sidenreng Rappang District.The population in this study is the total number of family heads in the village of Kalosi, amounting to 1,471 consisting of two hamlets. The sampling technique uses the Slovin formula with 93.63 results rounded up to 94, including 94 respondents, taken based on the Probability sampling technique, more precisely Random sampling. This type of research is quantitative descriptive. Data collection techniques used in this study were observation, questionnaire, literature study and documentation. The collected data is then analyzed using data analysis techniques using validity, reliability and regression tests with the help of the SPSS 16.0 program. Based on the results of the questionnaire, the influence of social stratification on public services has a significant effect on the results of the processed data in the ANOVA table. The value of t arithmetic = 9.340> t table = 3.179 with a significant value of 0,000 <0.05, then Ho is rejected and Ha is accepted, which means there is a significant (significant) social stratification variable (X) on public service variables (Y) and based on From the results of the questionnaire, the factors influencing social stratification can be seen from the first factor differences in race and culture have an influence of 50.2%, the second factor is the existence of specifications in the field of work, 19.2% and the third factor is the scarcity in society regarding the distribution of rights. and a liability of 13%. Keywords: Startification and service public